Memoria de actividades de la Fundación Francisco Largo Caballero 1978-2003 - Moral Sandoval, EnriqueMéndez, Cándido (1952-) Chaves González, ManuelRedondo, Nicolás (1927-) García Santesmases, AntonioAróstegui, Julio (1939-2013) Martínez Cobo, José (1933-) Martínez Cobo, Carlos (1932-2005) Gómez Llorente, LuisArango Fernández, JesúsFernández López, ManuelReyna Fernández, SebastiánSimón, ManuelZufiaur Narvaiza, José María
Contiene colaboraciones de Enrique Moral Sandoval, Cándido Méndez, Manuel Chaves, Nicolás Redondo, Antonio García Santesmases, Julio Arostegui, José Martínez Cobo, Carlos Martínez Cobo, Luis Gómez Llorente, Jesús Arango, Manuel Fernández Lito, Sebastián Reyna, Manuel Simón y José M° Zufiaur